The Role of Religion in Social Transformation: Challenge of Ushuluddin’s Studies in Globalization Era - IT, Suraiya (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2023)
Religion has plays a major role in influencing cultures and shaping social behavior. Religion, the faith in God, with all of the spiritual wealth, can influence people and even improve them until perfection. The science of Ushuluddin studies the basics of Islamic religious beliefs (Iman), and all matters related to faith, or Tawhid. The science of monotheism is also called the science of Ushuluddin (the basics or main points of religion) or the Science of Kalam. Therefore it is called the science of Ushuluddin (the matter subject of religion). Ushuluddin has to answered the problem of the Muslim Ummah. The interpretation of Ushuluddin is how the human relationship with God and man to man to avoid inequality, the human beings should be able to put himself as a servant of God are always subjecting themselves stopper form the ritual worship. Religious education aims to help to develop the ability of thinking, to testify values and to have complete knowledge concerning the modern world, to process critical attitude for social values, in order to develop civilization within multicultural society. This research tries to analyze the impact of Religion in social transformation as a challenge of Ushuluddin’s studies of globalization.